5y=(3y-5)

Simple and best practice solution for 5y=(3y-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y=(3y-5) equation:


Simplifying
5y = (3y + -5)

Reorder the terms:
5y = (-5 + 3y)

Remove parenthesis around (-5 + 3y)
5y = -5 + 3y

Solving
5y = -5 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
5y + -3y = -5 + 3y + -3y

Combine like terms: 5y + -3y = 2y
2y = -5 + 3y + -3y

Combine like terms: 3y + -3y = 0
2y = -5 + 0
2y = -5

Divide each side by '2'.
y = -2.5

Simplifying
y = -2.5

See similar equations:

| 4d^2+4d+100= | | (7t-1)-(8t+5)= | | (4b-4)(5b-6)= | | 5*(3.2-1.2B)+6B=16 | | 4y-2= | | -3y-4y(2+y)= | | (7x^2-x-2)-(-6x^3+3)= | | -2=4x+6+4 | | x*x*x-(2x^2+4)= | | -3(3r-8)=-36 | | -2=4+6+4 | | x^2+6x+42=0 | | (m^2-m-4)+(m-5)= | | 2x^2+6x-7x+8-3x^2+1= | | 5*(3.2+-1.2B)+6B=16 | | 3x^2+6-2x+5x-4x^2+9= | | 5x-4(4-x)=x+1 | | 5k-2k=-9 | | 5x-20=3x-8 | | 4g-2h=-4 | | (3v^5+8v^3-10v^2)-(-12v^5+4v^3+14v^3)= | | 2x+3-5x=2x-10-9x | | 7-(2-x)=2x | | 4(2x+3)-2x=4x+20 | | 54s^2-96st+42t^2= | | x^2-3x-7= | | (7-13x^3-11x)-(2x^3+8-4x^5)= | | 2(x-y)(x+y)= | | 8p=-96 | | 5a+6b=16 | | -9=-5n-4n | | -4a[-4(a-2+3b)-6b(a-2)]= |

Equations solver categories